Radial blast prediction for high explosive cylinders initiated at both ends - Anastacio, A.; Knock, Clare (Cranfield University, 2016)
This paper presents experimental results for the double ended initiation of cylindrical, explosive charges. Bare cylindrical charges of PE4 (RDX/binder 88/12 %) were used with length to diameter ratios of 1/3.7 to 5.75/1 and masses of 0.25 to 0.45 kg. Pressure measurements were taken at distances of 1 to 3.5 m in the radial direction. It was found that it was possible to predict the peak overpressure in the radial direction using P=K′M(L/D)1/3R−3. M is the mass of explosive, L the length of the explosive charge, D the diameter of the explosive charge, and R the distance from the charge. For PE4, K′=2251 kPa m3 kg−1 for all length to diameter ratios. The double ended initiation gives a peak overpressure 1.6 times that for single ended initiation. The impulse for double ended initiation was found to be the same as for single ended initiated charges.
Keywords: Cylindrical charges; Peak overpressure; Blast prediction; Impulse; Double ended initiation